Perancangan Aplikasi Kidung Pujian Berbasis Android - Adelhard Beni Rehiara (Jurnal Teknik Elektro dan Komputer, 2020)
The usage of smartphones has been spread widely and also its software has been well built. In this research a software application for Android smartphone has been developed using App Inventor program. The objective of this research is to support people in doing praising using Mazmur and Nyanyian Rohani as their hymns of praise. Result of simulation shows that this software can work in offline mode and it can run well even in a limited platform of both smartphones technology and Android version.